MEMAKNAI KEMISKINAN BERDASARKAN PANDANGAN ORANG MISKIN PEDESAAN - Silvana, Tine; Yusup, Pawit M; Subekti, Priyo (Edulib, 2014)
AbstractRural poverty can be understood as a social condition of a person, or a group of people who were associated with aspects of economic and non-economic aspects. Scientific aspects such as social, cultural, health, education, psychology, the environment, law, anthropology, and art, was often associated with poverty. Nevertheless, the notion of poor and rural poverty is, in general, is still viewed by researcher's perspective, rather than emic, ie see something from the perspective of the participant. This study took part of the effort to comprehensively understand the meaning of poor and poverty in the eyes of the poor, especially in rural areas, roomates point is on how to map view of rural poor people in hopes of interpreting experience of livelihood as poor in underlying survival living. By using a qualitative study approach, especially the tradition of phenomenology of Schutz, obtained a description of the results, that the meaning of poor and poverty, in phenomenology, containing context, such as: context ownership; contexts effort and trial and error; contexts powerlessness; contexts outside assistance; independence in the context of compulsion; contexts unattainable expectations; context of the struggle; context of limited access to information; contexts low curiosity; contexts simplicity needs; problems humiliation context; and context sensitivity in social communication.Keywords: Meaning poor, Poverty, RuralÂ AbstrakKemiskinan di pedesaan dapat dipahami sebagai suatu kondisi sosial seseorang, atau sekelompok orang yang terkait dengan aspek-aspek ekonomi dan non-ekonomi. Aspek ilmiah seperti sosial, budaya, kesehatan, pendidikan, psikologi, lingkungan, hukum, antropologi, dan seni, yang sering dikaitkan dengan kemiskinan. Namun demikian, gagasan tentang kemiskinan dan pedesaan, secara umum, masih dilihat dari perspektif peneliti, bukan emik, yaitu melihat sesuatu dari perspektif partisipan. Penelitian ini mengambil bagian dari upaya untuk secara komprehensif memahami makna miskin dan kemiskinan di mata masyarakat miskin, terutama di daerah pedesaan, which titik adalah bagaimana memetakan pandangan masyarakat miskin pedesaan dengan harapan pengalaman yang menafsirkan mata pencaharian sebagai masyarakat miskin untuk bertahan hidup. Dengan menggunakan pendekatan studi kualitatif, khususnya tradisi fenomenologi Schutz, diperoleh gambaran hasil, bahwa makna miskin dan kemiskinan, dalam fenomenologi, mengandung konteks, seperti: kepemilikan konteks; Upaya konteks dan trial and error; Ketidakberdayaan konteks; konteks di luar bantuan; kemerdekaan dalam konteks paksaan; konteks harapan tercapai; konteks perjuangan; konteks terbatasnya akses terhadap informasi; konteks rasa ingin tahu yang rendah; kesederhanaan konteks kebutuhan; konteks masalah penghinaan; dan sensitivitas konteks komunikasi sosial.Kata Kunci : Makna kemiskinan, Kemiskinan, Desa